2021
DOI: 10.3390/rs13234946
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Climate and Bioclimate on COVID-19 Cases in Poland

Abstract: The correlations between air temperatures, relative and absolute humidity, wind, cloudiness, precipitation and number of influenza cases have been extensively studied in the past. Because, initially, COVID-19 cases were similar to influenza cases, researchers were prompted to look for similar relationships. The aim of the study is to identify the effects of changes in air temperature on the number of COVID-19 infections in Poland. The hypothesis under consideration concerns an increase in the number of COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“… Wang Q et al [ 70 ] 2021 China January to October 2020 305 Spearman, linear regression 7 Temperature, wind speed, precipitation, air pressure The daily average temperature, wind speed, precipitation, and new COVID-19 cases were negatively correlated Sangkham S et al [ 71 ] 2021 Bangkok, Thailand January 1 to March 30, 2020 90 Kendal and Spearman's Rank correlation 7 Temperature, wind speed, rainfall, humidity Weather parameters such as temperature, relative humidity, and wind speed are positively associated with daily confirmed COVID-19 cases in the BMR. Werner PA et al [ 72 ] 2021 Poland March 2020 till July 2021 519 Pearson's correlation 6 Temperature The hypothesis under consideration concerns an increase in the number of COVID-19 cases as temperature decreases Sharif N et al [ 73 ] 2021 Japan January 2020 to February 2021 425 Spearman's rank correlation 6 Temperature (max, min, ave), precipitation, wind velocity, rainfall, and Relative humidity Relative humidity had the highest correlation with the case fatality rate. Sharif N and Dey SK [ 74 ] 2020 Bangladesh 07 March 2020 to 14 August 2020 161 Spearman rank correlation 6 Temperature (max, min, ave), wind speed, rainfall, relative humidity Among metrological parameters, the average temperature strongly correlated with the cases.…”
Section: Resultsmentioning
confidence: 99%
“… Wang Q et al [ 70 ] 2021 China January to October 2020 305 Spearman, linear regression 7 Temperature, wind speed, precipitation, air pressure The daily average temperature, wind speed, precipitation, and new COVID-19 cases were negatively correlated Sangkham S et al [ 71 ] 2021 Bangkok, Thailand January 1 to March 30, 2020 90 Kendal and Spearman's Rank correlation 7 Temperature, wind speed, rainfall, humidity Weather parameters such as temperature, relative humidity, and wind speed are positively associated with daily confirmed COVID-19 cases in the BMR. Werner PA et al [ 72 ] 2021 Poland March 2020 till July 2021 519 Pearson's correlation 6 Temperature The hypothesis under consideration concerns an increase in the number of COVID-19 cases as temperature decreases Sharif N et al [ 73 ] 2021 Japan January 2020 to February 2021 425 Spearman's rank correlation 6 Temperature (max, min, ave), precipitation, wind velocity, rainfall, and Relative humidity Relative humidity had the highest correlation with the case fatality rate. Sharif N and Dey SK [ 74 ] 2020 Bangladesh 07 March 2020 to 14 August 2020 161 Spearman rank correlation 6 Temperature (max, min, ave), wind speed, rainfall, relative humidity Among metrological parameters, the average temperature strongly correlated with the cases.…”
Section: Resultsmentioning
confidence: 99%
“…As the pandemic progressed, an increasing number of publications provided a literature review on the interaction between the natural environment and COVID-19 ( Shakil et al, 2020 ; Facciolà et al, 2021 ; Núñez-Delgado et al, 2021 ; Labib et al, 2022 ; Rahimi et al, 2021 ; Han et al, 2023 ) or focused on the analysis of the correlation between various components of the natural environment (atmosphere, hydrosphere, lithosphere, biosphere) and COVID-19 in specific geographical regions or countries ( Bashir et al, 2020b ; Sobral et al, 2020 ; Zhu et al, 2020 ; Song et al, 2022 ). A large impact on the spread of the virus as well as the number of infections was most often attributed to climatic factors ( Ahmadi et al, 2020 ; Islam et al, 2021 ; Werner et al, 2021 ; Akan, 2022 ). The international scientific literature emphasizes the key role of air quality and pollution (i.e., particulate matter, carbon monoxide, nitrogen dioxide, sulfur dioxide, ozone) in the spread and severity of COVID-19 in various world regions ( Kowalski et al, 2021 ; Maleki et al, 2021 ; Carballo et al, 2022 ; Perone, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the international scientific literature, there are only a few publications on the relationship between the geographical environment and COVID-19 in Poland that include meteorological and bioclimatic factors ( Kowalski et al, 2021 ; Werner et al, 2021 ) and green‒blue space ( Ciupa and Suligowski, 2021 ). Our research fits into the contemporary trend, showing the need to demonstrate the impact of the environment on the course of the COVID-19 pandemic ( Han et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Werner et al. [12] revealed that the number of COVID-19 infections is strongly correlated with the mean radiation temperature. The results of Khan et al.…”
Section: Introductionmentioning
confidence: 99%